México frente a los “refugiados de paz” de la Oficina Internacional del Trabajo: implicaciones político-diplomáticas de un (no) caso (1924-1929) - Herrera León, Fabián (Revista Complutense de Historia de América, 2025)
The exceptional effort of the International Labour Organization (ILO) in the resettlement of Russian and Armenian refugees from the first postwar period gave rise to an unexpected exchange with Mexico, then an internationally marginalized country because of its revolution. The efforts of the ILO, in favor of the “peace refugees”, directed privately by its first director, the French socialist Albert Thomas, would open an exceptional channel of communication and understanding that, apart from the small and still ambiguous number of stateless taken to Mexico, it would contribute to the regularization of the post-revolutionary regime in the face of Genevan multilateralism.